Nanosensor based detection of a species specific sequence related to ganoderma boninense gene - Haily Liduin Koyou (2015)
Ganoderma species belong to the group of Basidiomycetes, or club and mushroom, group of fungi. In palm oil plantations, the basal stem root (BSR) is the most serious disease that caused by Ganoderma boninense fungi. Traditional culturing methods which are time consuming, require 4-5 days preliminary result, are very problematic, highly prone to contamination, difficult to handle for large numbers of isolates and not suitable for on-site monitoring. On the other hand, DNA studies involving the use of polymerase chain reaction (PCR) face the difficulties to quantitatively analyze target genes because of contamination and non-linearities in amplification number with cycle number. The electrochemical biosensor based on multiwall carbon nanotubes, calcium oxide nanoparticles, chitosan and gold electrode was developed in detecting the specific sequence related to G.boninense gene. DNA probe had been immobilized on the modified electrode and the hybridization event was monitored. Under the optimum condition, different concentration of the target DNA was identified ranged from 1.00 x 10-11 M to 1.00 x 10-s M of Ganoderma boninense gene was performed. The correlation relationship of 0. 9784 and a detection limit of 3.08 x 10-11 M was obtained. Therefore, electrochemical biosensor based on multiwall carbon nanotubes, calcium oxide nanoparticles, chitosan and gold electrode was able to be used for routine identification of Ganoderma boninense as it is cheaper, easy and convenient.